Web-Based Marketplace Private Lesson Engingeering in Bandar Lampung - Halimah Yunus; Indera Indera; Sushanty Saleh; Handoyo Widi Nugroho (Prosiding International conference on Information Technology and Business (ICITB), 2022)
Education is the most important thing in our life. Every human being has the right to education and always develops in it. Along with the rapid development of the world of education, the paradigm of society which still considers that the quality of education of a student is the responsibility of the teachers at the school has now shifted. Problems that then arise through searches like this, among others, are the search for prospective private tutors that take It took quite a long time, it was difficult to find a suitable location and time between prospective tutors and students, could not find out the competencies, achievements, and track-records of prospective private tutors so it was difficult to find the best prospective private tutors. After identifying and making a design flow In the process of collecting data, the next step in the process of making this application is to determine the data source. Sources of data used in this study, mostly secondary data which is data that has been processed, data obtained by taking report data, notes and results of previous research or studies that are directly related to the problems discussed. The data sources include: literacy books, interviews and websites belonging to several experts. Implementation of research results is the stage where the system is ready to operate. The author carries out training for system users by providing sufficient understanding and knowledge about the position and function of the interface of the related information system. This system is shown to the admin or system manager. This is so that system users can understand system work procedures and reduce errors that hinder the smooth use of the system. The e-marketplace system created can make it easier for parents to find private teachers. The e-marketplace system provides many choices of private teachers who have criteria according to what consumers or parents need. The application of a website- based e-marketplace system also makes it easy for teachers to promote their expertise to be able to teach students privately according to their level of education and experience.Keywords— Teacher, Private, System, E-marketplace.